2006
DOI: 10.1111/j.1447-0756.2006.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial thickness screening in premenopausal women with abnormal uterine bleeding

Abstract: Endometrial thickness of 8 mm or less is less likely to be associated with malignant pathologies in premenopausal uterine bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 11 publications
3
37
1
4
Order By: Relevance
“…Mean endometrial thickness of <8mm is less likely to be associated with malignant pathology in perimenopausal age group which is consistent with the study by Getpook C et al, [11] they found that endometrial thickness of 8 mm or less is less likely to be associated with malignant pathologies in perimenopausal uterine bleeding. Most of the patients were diagnosed as Anovulatory DUB about 60% followed by Hyperplasia without atypia and Ovulatory DUB about 15% and 13.3% respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Mean endometrial thickness of <8mm is less likely to be associated with malignant pathology in perimenopausal age group which is consistent with the study by Getpook C et al, [11] they found that endometrial thickness of 8 mm or less is less likely to be associated with malignant pathologies in perimenopausal uterine bleeding. Most of the patients were diagnosed as Anovulatory DUB about 60% followed by Hyperplasia without atypia and Ovulatory DUB about 15% and 13.3% respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Endometrium equal to or thicker than 5 mm in the postmenopausal period was regarded as abnormal. (10)(11) In few patients, the technique was unsuccessful due to continuous leakage of saline through internal os. Few patients also complained of crampy lower abdominal pain, after which the procedure was temporarily stopped.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies in recent literature have indicated that saline infusion sonography can differentiate intracavitary masses from more diffuse endometrial thickening. (6)(7)(8)(9)(10)(11) This study was performed to evaluate the role of SIS in detecting the endometrial lesion in women with AUB and thickened endometrium. Although, the use of fluid enhancement in abdominal ultrasound was described both for uterine and tubal observations.…”
Section: Introductionmentioning
confidence: 99%
“…Higher values of EMT indicate endometrial hyperplasia or endometrial carcinoma. 16,17 This study is aimed at comparing the endometrial thickness as measured by TVS with histopathology of the endometrium in patients with PMB and to define a cut off value of EMT by plotting a Receiver Operating Characteristic curve (ROC) for identifying patients at risk for malignancy.…”
Section: Introductionmentioning
confidence: 99%